Human cloning in the light of the Islamic Jurisprudence - Alathamneh, Ghaidaa (Jordan Journal of Islamic Studies, 2023)
This research provides a jurisprudential study of human cloning, exploring its concept, types, underlying motivations, and the Islamic perspective on it based on the underlying reasons. The study reveals several key findings: Firstly, human cloning is driven by various motives. Second, asexual human cloning, accomplished using an ovum and a somatic cell, is prohibited if its aim is population increase or species enhancement. Third, human cloning, in both forms, is allowed for therapeutic stem cell purposes and cell replacement. Finally, sexual human cloning is permissible for obtaining multiple fetuses in specific medical conditions.